Debt Relief for the Poorest : An OED Review of the HIPC Initiative - Gautam, Madhur (Washington, DC: World Bank, 2013)
The review by the Operations Evaluation Department finds the Heavily Indebted poor Countries (HIPC) initiative highly relevant in addressing a key obstacle facing many poor countries. If the anticipated debt relief is delivered in full, the initiative will succeed in substantially achieving its fundamental goal of reducing the excessive debt burden of the qualifying countries. But the legitimizing process that helped make the initiative a reality has also expanded its objectives. The initiative seeks to provide a "permanent" exit from debt rescheduling, promote growth, and release resources for social expenditures targeted at poverty reduction. Achieving these objectives will require actions by donors and the HIPC governments that are beyond the scope and means of the initiative. Unmanageable debt is a problem that needs to be effectively dealt with, but it is also a result of economic and political factors constraining growth and poverty reduction. The HIPC Initiative is thus an important but small part of the overall development assistance framework. Having provided the HIPCs with an opportunity for a "fresh start," the international community still faces a challenge in helping these countries set out on a sustainable path for growth and poverty reduction.